Women Language ‘Hidden Figure’ Movie Script Written By Allison Shroeder and Theodore Melfi - Yuniar Fatmasari; Rita Gustina (Metaphor, 2020)
Many factors can affect the way people communicate. One of them is gender. Compared to the men, women tend to use many language variations. Understanding the language variation used by women is important, so that its language function. In this research, the writers analyze the women's language features used by female characters in "Hidden Figures" movie script written by A. Schroeder and T. Melfi together with its functions. The method of this research is descriptive qualitative research. The research’s results show that female characters in “Hidden Figures” movie use 28% lexical hedges (28 expressions), 2% tag question (2 expressions), 4% rising intonation on declaratives (4 expressions), 3% empty adjective (3 expressions), 36% intensifiers (35 expression), 1% hypercorrect grammar (1 expression), 17% superpolite forms (17 expressions), 4% avoidance of strong swear word (4 expressions), and 5% emphatic stress (5 expressions). Intensifier features is the most dominant in women language features realized in “Hidden Figures” movie script. Whereas the function of the language used by women here are referential functions, emotive functions and conative functions.